2015
DOI: 10.4315/0362-028x.jfp-14-176
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Escherichia coli O157:H7 and Salmonella in Camels, Cattle, Goats, and Sheep Harvested for Meat in Riyadh

Abstract: Escherichia coli O157:H7 and Salmonella are significant foodborne pathogens that can be found in the feces and on the hides of meat animals. When hides are removed during the harvest process, the carcass and subsequent meat products can become contaminated. Camels, cattle, sheep, and goats are harvested for meat in Riyadh, Saudi Arabia. The prevalence of E. coli O157:H7 and Salmonella are unknown in these animals, and it is assumed that if the animals carry the pathogens in their feces or on their hides, meat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
17
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 35 publications
(33 reference statements)
10
17
4
Order By: Relevance
“…The overall prevalence of E. coli O157/O145 in sheep at sale yards in this study (8.4%, point prevalence 0–26%) was comparable with a previous study in which E. coli O157 was isolated from the faeces of 5% of sheep, 3% of fleeces and 0.6% of pre‐chill carcases at two Australian abattoirs, but higher than that observed in a study that detected E. coli O157 in 2.5% in sheep faeces and 2.9% on hides at a Saudi Arabian abattoir . Other studies have reported prevalences of 0% in sheep from North Wales, 3.9% in sheep from Iran and 18% in sheep from Turkey …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The overall prevalence of E. coli O157/O145 in sheep at sale yards in this study (8.4%, point prevalence 0–26%) was comparable with a previous study in which E. coli O157 was isolated from the faeces of 5% of sheep, 3% of fleeces and 0.6% of pre‐chill carcases at two Australian abattoirs, but higher than that observed in a study that detected E. coli O157 in 2.5% in sheep faeces and 2.9% on hides at a Saudi Arabian abattoir . Other studies have reported prevalences of 0% in sheep from North Wales, 3.9% in sheep from Iran and 18% in sheep from Turkey …”
Section: Discussionsupporting
confidence: 87%
“…The overall prevalence of S. enterica (3.6%, point prevalence 0–6.4%) was comparable with a longitudinal study that found the S. enterica point prevalence ranged from 0% to 24% in lambs on farms across Australia, but lower than that observed in studies that identified Salmonella in 20% of faecal samples, 13% of fleeces and 1.3% of pre‐chilled carcases at two Australian abattoirs, and 23.2% of faecal samples and 67.6% of hides at an abattoir in Saudi Arabia …”
Section: Discussioncontrasting
confidence: 64%
“…Our results showed that the highest prevalence occurred in spring and early summer months (February to April) which was likely due to the intense heat during summer months in UAE when daytime temperatures may reach as high as 50 °C which causes E. coli 0157:H7 prevalence to decline due to its inability to persist in the extreme environment. These results are in agreement with previous studies carried out in Riyadh, Saudi Arabia, where the highest prevalence was reported in spring and early autumn months [27]. In fact we were unable to detect E. coli O157:H7 in any other months as was also reported in other parts of the world.…”
Section: Discussionsupporting
confidence: 93%
“…Hence, our observed E.coli O157:H7 prevalence in the UAE slaughterhouse is in agreement with previous studies carried out in various countries like Ethiopia, South Africa, United Kingdom and Ireland where the prevalence of E. coli O157:H7 at abattoir level was reported as 2.7, 2.8, 2.9, 3.2 and 3.0% [22,23,24,25,26]. Further, the highest prevalence of E. coli O157 (4.3%) was identified in camel feces compared to the other animals, which was similar to reports carried out in neighboring countries including Riyadh, Saudi Arabia, where the prevalence in camel feces was 2.4% [27]. Alternatively, our reported prevalence was found to be slightly lower compared to those reported in Ethiopia (8%) and Iran (6.4-9.6%) [28,29].…”
Section: Discussionsupporting
confidence: 83%
“…Artiodactyla usually carry bacteria in their gastrointestinal tract with no symptoms [1], which is supported by the results of this study. Moreover, they have been subjected to greater exposure to enterobacteria than other confined animals investigated to date.…”
supporting
confidence: 85%